Empowering Education: Examining the Impact of Female School Leaders on Inclusive Practices in Sharjah Schools - ABDELWAHAB, RADWA SHAKER (2024)
This comprehensive research delves into the profound influence of women in leadership roles within the educational landscape of schools across Sharjah. The primary thrust of this investigation is to dissect and understand the multitude of strategies these leaders employ in their relentless pursuit of inclusivity. With a laser-sharp focus on these strategies, the research aims to comprehend their intricacies, evaluate their tangible and intangible impact on teachers and staff, and propose innovative methods that could further bolster the cause of inclusivity. To ensure a well-rounded understanding, the investigation does not limit itself to a single method of research. Instead, it adopts a multi-faceted approach, employing a blend of qualitative interviews and surveys. These tools provide a platform for a rich and nuanced collection of data, leading to a more holistic understanding of the situation at hand. The expected outcomes of this research are set to throw a spotlight on the pivotal and often underappreciated role of women school leaders. It anticipates demonstrating how these leaders are instrumental in crafting inclusive environments within schools. Their influence extends beyond policy and reaches into the heart of the school ecosystem, impacting the relationships among teachers and staff. Moreover, the study expects to underscore how this leadership and the resulting inclusivity are key drivers propelling advancements in educational outcomes. The broader implications of this study are far-reaching. By showcasing the potential for enhancing leadership practices and policies, the research hopes to foster a more inclusive and equitable school setting. It aims to inspire a shift in traditional paradigms, encouraging the adoption of more inclusive practices on a wider scale, potentially influencing educational systems beyond Sharjah. Keywords: women in leadership roles, inclusive educational methods, leadership tactics, dynamics between teachers and staff, diversity, educational results, policy enhancement, educational paradigm shift.